Musical hallucination or musical obsession? A differential diagnosis between two cases - Costa, Octavio Pennella Fenelon [UNESP]; Dalcim, Maria Luiza [UNESP]; Smaira, Sumaia Inaty [UNESP]; Lovadini, Gustavo Bigaton [UNESP] (FapUNIFESP (SciELO), 2024)
Musical hallucinations and musical obsessions are distinct phenomena. The first can be understood as a manifestation of the musical ear syndrome, which produces deafferentation auditory hallucinations, while the latter is an obsessive symptom of obsessive-compulsive disorders. Both symptoms are often poorly understood and mistaken for one another or for signs of psychotic disorders. We report two cases, one characterized by musical hallucinations and the other by musical obsessions, both with comorbid hearing impairment, which is the main confounding factor in their differential diagnosis. We critically compare the two cases and their key features, allowing diagnostic differentiation and a targeted therapeutic approach.
Alucinação ou obsessão musical? Um diagnóstico diferencial entre dois casos
Keywords: Charles Bonnet Syndrome; Hallucinations; Hearing Impairment; Obsessive Behavior; Obsessive-Compulsive Disorders